THE EFFECTOF WORK LIFE QUALITY, WORK CULTURE, WORK MOTIVATION, AND RELIGIUSITY ON STAFFS PERFORMANCE - Nury Yasien Rachmatullah; Muhaimin Dimyati; Zainollah Zainollah (STIE Mandala Jember, 2019)
This empirical investigation aimed to determine the effectof work life quality, work culture, work motivation, and religiusity on the staffsperformance in SD Al BaitulAmien (full day school) Jember. Population of this study was all tachers in SD Al BaitulAmien (full day school) Jembertotaling 20 persons used for the sample.Data were collected with a questionnaireusing a Likert scale. Then theywere analyzed using correlation and regressiontechniques using Statistical Package For Social Science (SPSS)program version23.0.The study found that : 1) Quality of working life (QWL) has a positive effect onthe performance of staffs in the SD Al BaitulAmien (full day school) Jember. 2) theworkmotivation has a positive effect onthe staffsperformance in the SD Al BaitulAmien (full day school) Jember.3) Work culturehaspositive effect on staff performance in SD Al BaitulAmien (full day school) Jember. 4) Religiosity have a positive effect on staff performance in SD AlBaitulAmien (full day school) Jember. The findings of this study provide practical advice to staffs and principals to be able to enhance SD Al BaitulAmien (full day school) Jember. Quality of working life, work culture, motivation and religiosity in orderto optimize the performance of staff increased at SD Al BaitulAmien (full day school) Jember.